2006
DOI: 10.1002/cncr.21775
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and prognostic relevance of disseminated tumor cells in bone marrow of patients with metastatic renal cell carcinoma

Abstract: Objective In humans, abnormal neuronal migration and severe neuronal disorganization resulting from Lis1 (lissencephaly) haploinsufficiency contributes to cognitive impairment and seizures early in life. In Lis1 heterozygotic mice, severe hippocampal disorganization and cognitive impairment have also been reported. Using this mouse model, we examined the functional impact of LIS1 deficiency with particular focus on excitatory glutamate‐mediated synaptic transmission. Methods We used visualized patch‐clamp reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…At the follow-up (median, 40 months) 14% of patients with CK+ disseminated tumor cells in their bone marrow suffered from tumor progression in contrast to 11% of patients without CK+ disseminated tumor cells. There is only one report to date, by Buchner and coworkers (20), that shows that detection of disseminated tumor cells in metastatic renal cell carcinoma patients is an independent prognostic factor. They detected CK+ circulating tumor cells in bone marrow samples of 42% of M 1 patients and in 25% of M 0 renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the follow-up (median, 40 months) 14% of patients with CK+ disseminated tumor cells in their bone marrow suffered from tumor progression in contrast to 11% of patients without CK+ disseminated tumor cells. There is only one report to date, by Buchner and coworkers (20), that shows that detection of disseminated tumor cells in metastatic renal cell carcinoma patients is an independent prognostic factor. They detected CK+ circulating tumor cells in bone marrow samples of 42% of M 1 patients and in 25% of M 0 renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others have reported that the presence of disseminated tumor cells is not convincingly associated with worse survival in operable breast cancer patients (8,18,19). In addition, the prognostic relevance of detection of disseminated tumor cells in the bone marrow of metastatic renal cell carcinoma patients has also been recently shown (20). However, the prognostic impact of circulating tumor cell detection in peripheral blood of renal cell carcinoma patients has not yet been determined.…”
Section: Introductionmentioning
confidence: 97%
“…Investigations in patients with different tumours have assessed the prognostic value of disseminated epithelial cells in bone marrow and peripheral blood detected by immunocytochemistry using anti-cytokeratin antibodies [46-48]. Only a few studies in RCC patients have demonstrated the possibility of cytokeratin-positive (CK+) cells as markers for CTCs investigated independently in peripheral blood and bone marrow [49,50]. An increase in the number of CK+ cells in RCC patients correlates with advanced tumour stage in RCC [51].…”
Section: Introductionmentioning
confidence: 99%
“…However, in another study, Buchner et al [50] found the prognostic values of disseminated CK+ cells in the bone marrow of patients with metastatic RCC indicated that these cells played an important role in tumour spread in metastatic RCC. The researchers also found that immunocytochemical detection of these cells could be useful in the assessment of clinical outcomes in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Clear cell RCC (ccRCC) is the most common and the most aggressive subtype of this disease [3]. About one third of the patients already present distant metastases at the time of diagnosis, whereas nearly another third develops metastases during the course of the disease [1, 4]. Although the application of target-directed therapeutics improved the outcome of patients with metastatic ccRCC their prognosis remains unfavourable [5].…”
Section: Introductionmentioning
confidence: 99%